In-vivo measurement of swine myocardial resistivity - Tsai, Jang Zern; Will, James A.; Stelle, Scott Hubbard Van; Cao, Hong; Tungjitkusolmun, Supan; Choy, Young Bin; Haemmerich, Dieter; Vorperian, Vicken R.; Webster, John G. (My University, 2002)
We used a four-terminal plunge probe to measure myocardial resistivity in two directions at three sites from the epicardial surface of eight open-chest pigs in-vivo at eight frequencies ranging from 1Hz to 1 MHz. We calibrated the plunge probe to minimize the error due to stray capacitance between the measured subject and ground. We calibrated the probe in saline solutions contained in a metal cup situated near the heart that had an electrical connection to the pig's heart. The mean of the measured myocardial resistivity was 319 Ω cm at 1 Hz down to 166 Ωcm at 1 MHz. Statistical analysis showed the measured myocardial resistivity of two out of eight pigs was significantly different from that of other pigs. The myocardial resistivity measured with the resistivity probe oriented along and across the epicardial fiber direction was significantly different at only one out of the eight frequencies. There was no significant difference in the myocardial resistivity measured at different sites.
Keywords: Calibration; Four-terminal; Heart; In-vivo; Leakage current; Myocardium; Pig; Plunge probe; Probe constant; Resistivity; Stray capacitance